Rolled vs. finely ground pelleted sorghum rain in cattle rations - Richardson, D.; Smith, E.F.; Koch, B.A.; Tsien, W.S.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This is a progress report of another test to further evaluate methods of sorghum grain preparation. Twenty of the heaviest steer calves purchased for experimental work were divided into two lots of 10 animals each. The daily ration is shown in Table 27. The only difference in the ration is that lot 3 received rolled sorghum grain and lot 4 finely ground pelleted sorghum grain. The gains and feed efficiency up to this time are essentially the same. The feed cost per 100 pounds gain is exactly the same. After completing the wintering phase, these animals will receive a fattening ration.
Keywords: Beef; Rolled vs. finely ground pelleted sorghum